2015
DOI: 10.1557/opl.2015.563
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sputtering Deposited 2-Dimensional MoS2 Film by Raman Spectroscopy

Abstract: Molybdenum disulfide (MoS2), one of the transition-metal dichalcogenides, is a 2-dimensional semiconducting material that has a layered structure. Owing to excellent optical and electronic properties, the ultra-thin MoS2 film is expected to be used for various devices, such as transistors and flexible displays. In this study, we investigated the physical and chemical properties of sputtered-MoS2 film in the sub-10-nm region by Raman spectroscopy and X-ray photoelectron spectroscopy (XPS). As the results of Ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…[4][5][6][7] This method can produce large scale uniform thin film at low temperature and accurately control film thickness by duration of sputtering time. 8,9 Although sputtering process tends to cause deviation from stoichiometry due to re-evaporation from the substrate in general and produces sulfur deficient MoS x (x<2) films, [10][11][12] we achieved to fabricate highquality sputtered MoS 2 atomically thin film by postdeposition sulfurization annealing (PSA) and confirmed superior electrical properties of the film applicable for TFT LCD with 8 K resolution. 13,14 In this study, we investigated large scale uniformity of sputtered single-and few-layer MoS 2 in further detail.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…[4][5][6][7] This method can produce large scale uniform thin film at low temperature and accurately control film thickness by duration of sputtering time. 8,9 Although sputtering process tends to cause deviation from stoichiometry due to re-evaporation from the substrate in general and produces sulfur deficient MoS x (x<2) films, [10][11][12] we achieved to fabricate highquality sputtered MoS 2 atomically thin film by postdeposition sulfurization annealing (PSA) and confirmed superior electrical properties of the film applicable for TFT LCD with 8 K resolution. 13,14 In this study, we investigated large scale uniformity of sputtered single-and few-layer MoS 2 in further detail.…”
mentioning
confidence: 70%
“…1, 3, and 5L MoS 2 films were fabricated on a SiO 2 (400 nm)/Si substrate (0.5 × 2.0 cm) by sputtering deposition from an 80 mmφ MoS 2 target (99.79% pure) at 300 • C and subsequential PSA at 500 • C using di-tertiary-butyl disulfide [(t-C 4 H 9 ) 2 S 2 ] as a sulfur precursor, which has sufficiently high vapor pressure (2.7 kPa at 84 • C). 8,12,13 The layer number of the films were controlled by adjusting the sputtering duration. The target-substrate distance was 150 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the number of grains and line defects are intrinsically formed during CVD synthesis, 23−25 which could degrade the electrical or mechanical performance. 26−28 To repair these grain boundaries and defects, a few posttreatments have been experimentally suggested, such as a postdeposition sulfurization annealing, 29 thermal annealing, 30 laser heating, 31 and electron beam irradiation. 32 As such, it is essential to investigate effective post-sulfurization strategies for CVD synthesis toward higher-quality TMDC materials.…”
mentioning
confidence: 99%
“…[14][15][16] On a separate note, Ishihara et al mentioned that the sputtering method is another candidate because of its larger-scale uniformity, more accurate thickness controllability, and greater suppression of impurity amounts than in other methods. 17) Therefore, we employed a sputtering method to form MoS 2 films [18][19][20] and found that a multilayered MoS 2 film was formed on an SiO 2 film with a carrier density 10 3 times smaller than that of an exfoliated MoS 2 film. 21) Researchers have focused on various aspects for further improvement of the electrical characteristics of MoS 2 films: many researchers stress the importance of the substrate surface roughness when examining layered films.…”
mentioning
confidence: 99%